Stick–slip vibration of a friction damper for energy dissipation. (July 2017) - He, Bingbing; Ouyang, Huajiang; He, Shangwen; Ren, Xingmin
This article studies energy dissipation of a friction damper (due to stick–slip vibration) in the context of harmonic excitation. There are numerous applications of such friction dampers in engineering. One particular example is a new kind of under-platform dry friction dampers for aero engines. The model consists of a clamped cross-like beam structure and two masses (friction dampers) in contact with the short beam of the cross. The two masses are allowed to slide along two extra short vertical clamped beams. They can exhibit three distinct dynamic regimes: pure slip, pure stick and a mixture of stick–slip relative to the short horizontal beam. The finite element method is used to obtain the numerical modes of the structure. The friction at the contact interface between the short horizontal beam and the friction dampers is assumed to follow the classical discontinuous Coulomb friction law in which the static coefficient of friction is greater than the kinetic coefficient. Modal superposition method is applied to solve the dynamic response of the structure with numerical modes. One major finding of this investigation is that there is an intermediate range of the normal contact forces (in stick–slip regime) that provides the best energy dissipation performance.